A hospital-based study for comparison of RIPASA score and modified ALVARADO score in diagnosis of acute appendicitis - Desai, Vishal M.; Vasaiya, Mehulkumar K. (International Surgery Journal, 2025)
Background: Acute appendicitis is a common cause of emergency abdominal surgery. Delayed or inaccurate diagnosis may lead to increased morbidity and healthcare costs. Scoring systems like the Modified Alvarado Score (MAS) and the RIPASA score have been developed to enhance diagnostic accuracy. This study aimed to compare the diagnostic performance of RIPASA and Modified ALVARADO scoring systems, with histopathological findings as the gold standard. Methods: A prospective comparative study was conducted at GMERS Medical College and Hospital, Himmatnagar, including 100 adult patients presenting with right iliac fossa pain and suspected acute appendicitis. Each patient was assessed using both scoring systems. Decisions for surgery were made independently by experienced surgeons. The final diagnosis was confirmed via histopathological examination. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy were calculated for each scoring system. Results: The mean age of patients was 27.32 years; 64% were male. Histopathological confirmation of appendicitis was found in 75% of cases. The Modified Alvarado Score demonstrated a sensitivity of 58.7%, specificity of 88%, PPV of 93.6%, NPV of 41.5% and diagnostic accuracy of 66%. In comparison, the RIPASA score showed higher sensitivity (89.3%), specificity (84%), PPV (94.4%), NPV (72.4%) and diagnostic accuracy (88%). ROC curve analysis also favoured the RIPASA score (AUC=0.891) over the Modified ALVARADO Score (AUC = 0.702). Conclusions: The RIPASA score outperformed the modified ALVARADO score in diagnosing acute appendicitis, offering superior sensitivity, NPV and overall diagnostic accuracy. Given its applicability using basic clinical and laboratory data, the RIPASA score is particularly valuable in emergency and resource- limited settings to guide timely surgical decisions and reduce unnecessary imaging or admissions.